Mid-Holocene El Nino-Southern Oscillation (ENSO) attenuation revealed by individual foraminifera in eastern tropical Pacific sediments - Koutavas, A.; deMenocal, P. B.; Olive, G. C.; Lynch-Stieglitz, J. (Geology, 2006)
Holocene reconstructions of the Ell Nino-Southern Oscillation (ENSO) provide valuable perspective on its recent evolution and can be important for assessing its future. Optimal assessment of past ENSO variability requires observations from its center of action in the eastern equatorial Pacific, but these are limited due to paucity of high-resolution paleoceanographic archives (e.g., corals). Here we use a new approach to quantify past ENSO variance based on the oxygen isotopic composition (delta O-18) of individual foraminifera (Globigerinoides ruber) from deep-sea sediments in the ENSO source region.. Individual G. ruber foraminifera behave as monthly recorders of sea-surface conditions, including ENSO extremes, circumventing the lack of annual resolution in the sediments. Intrapopulation delta O-18 distributions derived with this method from a core near the Galapagos Islands reveal mid-Holocene reductions in variance or 50%, requiring drastic attenuation of the ENSO amplitude. Furthermore, Mg/Ca thermometry indicates that mid-Holocene background conditions were accompanied by a stronger zonal temperature gradient that coincided with a northward-displaced Intertropical Convergence Zone (ITCZ). The results suggest that the position of the ITCZ is an important factor in the low-frequency modulation of ENSO and could influence its future evolution.
113wzTimes Cited:128Cited References Count:26